The dynamics of the plankton community on Lake Siombak, a tropical tidal lake in North Sumatra, Indonesia - Ahmad Muhtadi Rangkuti; AHYAR PULUNGAN; NURMAIYAH NURMAIYAH; AZIZAH FADLHIN; PUPUT MELATI; RENI ZULIKA SINAGA; RAIHAN ULIYA; MIFTAH RIZKI; DAYUN IFANDA; RUSDI LEIDONALD; HESTI WAHYUNINGSIH; QADAR HASANI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Muhtadi A, Pulungan A, Nurmaiyah, Fadlhin A, Melati P, Sinaga RZ, Uliya R, Rizki M, Rohim N, Ifanda D, Leidonald R, Wahyuningsih H, Hasani Q. 2020. The dynamics of the plankton community on Lake Siombak, a tropical tidal lake in North Sumatra, Indonesia. Biodiversitas 21: 3707-3719. The tidal lake is a very dynamic estuary ecosystem and very vulnerable to environmental stresses and disturbances. Plankton is an aquatic organism that is very easily affected by environmental pressures and disturbances. This study aimed to reveal the phenomenon of plankton dynamics in tropical tidal lakes in Indonesia. The study was conducted at Siombak Lake from September 2018 to August 2019. Data were collected at high and low tides every month during the full month. The data analysis included plankton abundance, diversity index, and the relationship between water quality and plankton with PCA and succession analysis. The results showed that in Siombak Lake was found 66 genera which consisted of 54 phytoplankton genera and 12 zooplankton genera. Plankton abundance is higher in parts of the lake (stations 1-8) than in the river (stations 9-11) at both high and low tide. Temporally it shows that plankton abundance is higher in the rainy season (Feb-Aug, outside May) than in the rainy season (Sep-Jan, and May). Spatially, plankton in Siombak Lake at high tide is more influenced by TSS, phosphate, and salinity, while at low tide, it is influenced by TSS, Water transparency, BOD, silicate, salinity, and dissolved oxygen. Temporally, plankton in Siombak Lake at high tide is more influenced by salinity, conductivity, Debit, TSS, and salinity, while at low tide, it is influenced by salinity, conductivity, turbidity, TSS, TDS, DO, BOD, and COD. Based on the plankton Frontier succession graph, it shows that Siombak Lake is included in stage 1 and stage 2. Stage 1 occurs before the rainy season (August-September) and the peak of the dry season (March-April).